Effect of simple omentoplasty and omentopexy in the prevention of complications after pelvic lymphadenectomy. Issue 1 (1st January 2003) - Fujiwara, K.; Kigawa, J.; Hasegawa, K.; Nishimura, R.; Umezaki, N.; Ando, M.; Itamochi, H.; Yamaguchi, S.; Oda, T.; Terakawa, N.; Kohshima, I.; Kohno, I.
Abstract : This multicenter collaborative study prospectively evaluated the effect of omentoplasty and omentopexy on the prevention of complications after pelvic lymphadenectomy. Sixty-four consecutive patients (42 cervical and 22 endometrial cancer) were enrolled and examined periodically for 12 months. All patients underwent simple, semiradical, or Okabayashi's radical hysterectomy and complete pelvic lymphadenectomy. The infracolic omentum was longitudinally divided in half and omentoplasty was performed so that bilateral omental flaps would reach the pelvic floor. The omental flaps were inserted into the retroperitoneal space and the edges of the flaps were sutured to the psoas muscle. The omental flap was then covered by the peritoneum. Incidence of lymphocele, lymphedema, and severe complications associated with lymphocele, such as infection or urinary stenosis, was evaluated at intervals for at least one year after surgery. Among the 64 patients, 12 patients received pelvic radiation because of occult lymph node metastasis. Planned omentoplasty was not possible in one patient because her omentum was too small; therefore, only unilateral omentopexy was performed. Asymptomatic lymphoceles only were detected by ultrasonogram in 12 patients (18.8%). Three patients (4.7%) had a symptomatic but pressure-only lymphocele. Hydronephrosis and bladder compression probably due to lymphocele were observed in one patient, respectively (3.1%), but resolved within 6 months. Lymphedema was observed in seven patients (10.9%) and persisted for more than 6 months in two patients (3.1%). We conclude that this simple technique of omentoplasty and omentopexy appeared to be effective in reducing the incidence of complications after pelvic lymphadenectomy.